1983
DOI: 10.1136/bmj.286.6363.425
|View full text |Cite
|
Sign up to set email alerts
|

Family study of the major histocompatibility complex in patients with systemic lupus erythematosus: importance of null alleles of C4A and C4B in determining disease susceptibility.

Abstract: The families of 29 patients with systemic lupus erythematosus and 42 normal subjects were studied to determine the inheritance of the HLA-A, B, C, and DR antigens and also the complement polymorphisms for C2, C4A, C4B, and Bf, which are encoded in the same region of the sixth chromosome. Null (silent) alleles for C4A, C4B, or C2 were found in 24 of the 29 (83%) patients compared with 18 of the 42 (43%) normal controls. HLA-DR3 was present in 20 (69%) of the patients and seven out of 39 (18%) of the normal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
162
1
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(171 citation statements)
references
References 19 publications
6
162
1
2
Order By: Relevance
“…No significant associations with other alleles at the C4 loci, or with Bf alleles, were found in SSc, althoygh the frequency of the factor B allele, BfF, was increased (38%). In contrast to the normal controls (3,13), in the patients with SSc, the inheritance of C4A"QO was not so strongly associated with HLA-B8 and DR3, but as expected, all the B8, DR3 haplotypes in the patients carried C4A*QO. Although these results were based on only 50 haplotypes (from 25 patients), it was apparent that the increased frequency of C4A*QO was not dependent on, or concomitant with, an increased frequency of B8, DR3.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…No significant associations with other alleles at the C4 loci, or with Bf alleles, were found in SSc, althoygh the frequency of the factor B allele, BfF, was increased (38%). In contrast to the normal controls (3,13), in the patients with SSc, the inheritance of C4A"QO was not so strongly associated with HLA-B8 and DR3, but as expected, all the B8, DR3 haplotypes in the patients carried C4A*QO. Although these results were based on only 50 haplotypes (from 25 patients), it was apparent that the increased frequency of C4A*QO was not dependent on, or concomitant with, an increased frequency of B8, DR3.…”
supporting
confidence: 55%
“…All but 2 of the 22 patients typed for both C4 and DR alleles had either C4A*QO or DR5, compared with 12 of 39 of the controls described by Fielder et a1 (13); this finding was highly significant (2 = 18.1, Pcorr = 0.005). The frequency of C4A*QO, the null variant of the second C4 locus, was normal, except that 2 of 25 of the patients were homozygous for this allele and were therefore deficient of C4B.…”
mentioning
confidence: 71%
“…In a number of recent studies, an increase in the frequency of C4A-null (C4A*pO) genes in Caucasian patients with SLE has been found (20,26,27,(32)(33)(34)(35)(36)(37)3942). Data from some of these studies are shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Detection is considerably improved by the use of family studies. Families of SLE patients have, in fact, been included in several studies (27,34,53). Some, but not all, C4A-null genes can be detected by Southern blotting, using Tuq I digestion of genomic DNA and a 5' complementary DNA C4 probe (55,56) Critical to the evaluation of the frequency of an MHC allele or haplotype in patients is the determination of control frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of C4A, so called C4Anull, is probably the most commonly inherited complement deficiency, occurring in varying frequency in different populations [44]. In some populations 50% to 80% of the SLE patients have a deficiency of C4A [31,38,[44][45][46][47]. The molecular basis of the C4A deficiency is heterogeneous, but the most common C4Anull allele in Caucasians is a 28-kb deletion removing both the C4A and 21-OHA genes, which occurs on the HLA B8-DR3 haplotype [40,45,48,49].…”
Section: Studies Of Candidate Genesmentioning
confidence: 99%